EDUCAÇÃO AMBIENTAL EM UNIDADES DE CONSERVAÇÃO URBANAS: DESAFIOS E POTENCIALIDADES NO CONTEXTO DE CAMPO GRANDE (MS) - PAOLA VICENTINI BONI (2025)
Environmental education is understood as a collective process that develops social values, knowledge, skills, attitudes, and competencies aimed at the conservation of the environment—recognized as an essential common good—with the goal of ensuring a healthy quality of life and socio-environmental sustainability. In this context, the connection between environmental education and conservation units, especially state parks, enables the development of conscious and meaningful environmental educational practices. This research aims to analyze the potential and challenges in the development of environmental education within urban conservation units, focusing on the Matas do Segredo State Park and the Prosa State Park, both located in the city of Campo Grande, in the state of Mato Grosso do Sul, Brazil. The methodology was structured in three stages: documentary analysis of the parks' management plans; analysis of the socioeconomic and environmental diagnostics of the surrounding areas; and the application of semi-structured interviews with Geography teachers, as well as questionnaires with students, whose data were analyzed through a qualitative and quantitative approach supported by statistical tests. The results indicate that, although the updated management plans have improved physical infrastructure, there are still significant gaps in the integration of critical educational actions. Socio-environmental disparities were also observed between the parks: Matas do Segredo Park, located in a peripheral area, shows greater tree cover and lower average income; whereas Prosa Park, situated in a central region, has lower vegetation coverage and higher purchasing power in its surroundings. It was also found that a conservative approach to environmental education predominates in schools, and that the parks are not used as recommended by the National System of Conservation Units (SNUC). Identified obstacles include logistical challenges, lack of awareness, and excessive bureaucracy, which limit the use of these spaces as non-formal learning environments. It is concluded that the articulation between environmental education and the pedagogical use of state parks remains insufficient, highlighting the need to revise the guidelines of these units in collaboration with the responsible authorities. The reformulation of public policies focused on teacher training can strengthen the sense of belonging within the school community and expand the educational use of these protected areas, thus promoting sustainability and a deeper connection between society and nature in urban contexts.